Development of Local Wisdom-Based Physics E-Modules to Improve Students Critical Thinking and Scientific Argumentation Skills on Newtonian Mechanics Topics - Briliantama Akbar Taufiq; Hidayatullah Hana Putra; Trisya Afidah Sukma (Graduate School of Universitas Negeri Malang, 2023)
The results of the identification of the objective conditions of learning in schools show problems, including students who memorize the material, but do not understand and are unable to connect physics material with the application of local wisdom in everyday life. This study aims to develop a local wisdom-based physics e-module product that was developed in terms of the components of illustration presentation, language, and material suitability for students' critical thinking and scientific argumentation skills on the Newtonian mechanics topics. Product development refers to the ADDIE research model (Analysis, Design, Develop, Implementation, Evaluation). The results of validation by material experts show that the local wisdom-based physics e-module developed has an average percentage of 93.83% (very valid), from media experts at 84.72% (quite valid), and learning experts at 97.22 % (very valid). Therefore, the overall average of the results of the local wisdom-based physics e-module media assessment by the experts is 92.59% with a very valid category. The developed e-module learning media received very good responses from students. This can be seen from the average student response of 90.61% (very good). Based on the validation results from the experts, the product in the form of a physics e-module local wisdom-based is very valid to be used in the learning process.